Prevalence and risk factors for vitamin D deficiency in long‐term childhood cancer survivors. Issue 7 (6th April 2021) - Bhandari, Rusha; Teh, Jennifer Berano; Herrera, Claudia; Echevarria, Meagan; Lindenfeld, Lanie; Wong, F. Lennie; Wilson, Karla; Armenian, Saro H.
Abstract: Background: Childhood cancer survivors (CCS) have increased risk of developing chronic health conditions, including musculoskeletal disorders. Little is known regarding vitamin D deficiency (VDD, <20 ng/ml) and its association with bone mineral density (BMD) in long‐term CCS. We evaluated the prevalence and risk factors for VDD in a large, diverse population of long‐term CCS, and examined the association between VDD and BMD in patients who underwent guideline‐recommended dual‐energy X‐ray absorptiometry (DXA) screening. Methods: This cross‐sectional study included 446 consecutive CCS seen from March 2018 to September 2020. Univariate analyses examined associations between CCS demographics, socioeconomic status, and treatment exposures and VDD. Multivariable logistic regressions identified factors associated with odds of VDD and reduced BMD. Results: Median age at evaluation was 27.5 years (range 7–67 years); median time from completing therapy was 14.2 years (range 2–65 years). Fifty percent were female, and 45% were Hispanic. Twenty‐four percent had VDD. In multivariable analysis, overweight and obese BMI were associated with VDD (overweight: OR 1.78, 95% CI 1.03–3.07, p = 0.04; obese: OR 2.40, 95% CI 1.39–4.13, p < 0.01; reference: normal/underweight), as was Hispanic or black race/ethnicity (OR 2.40, 95% CI 1.41–4.09, p < 0.01; reference: non‐Hispanic white). In the 118 CCS with DXA results, VDD was independently associated with reduced BMD (OR 3.58, 95%CI 1.33–9.59, p = 0.01). Conclusions: CCS have a high prevalence of VDD. High BMI and Hispanic or black race/ethnicity were associated with VDD. Survivors with VDD had a greater than threefold risk of reduced BMD. Risk‐based screening may facilitate timely interventions to mitigate VDD and improve BMD in CCS.